2023
DOI: 10.1101/2023.03.01.23286513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Third and fourth vaccine doses broaden and prolong immunity to SARS-CoV-2 in immunocompromised adult patients

Abstract: BackgroundPrevious studies have reported impaired humoral responses after SARS-CoV-2 mRNA vaccination in immunocompromised patients with immune-mediated inflammatory diseases (IMID), particularly those treated with anti-tumor necrosis factor (TNF) biologics. We previously reported that IMID patients exhibited greater waning of antibody and T cell responses compared to healthy controls after dose 2. Fewer data are available on the effects of third and fourth doses.MethodsThis observational cohort study collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…While vaccines may be sufficient to safeguard most immunocompetent individuals against severe COVID-19, the risk for the immunocompromised individuals described in this study underscores the urgent need for additional preventive measures against COVID-19 in this vulnerable population. The impact of COVID-19 on immunocompromised individuals is not surprising, as they are known to have impaired immune responses to vaccines, including lower antibodies levels, reduced neutralisation activity, 37 and shorter duration of protection, 22 often remaining insufficiently protected even after booster doses. 22 , 23 Previous retrospective cohort studies in Canada 24 and the United Kingdom, 38 , 39 which included the early phase of the Omicron period, showed that fully vaccinated immunocompromised individuals were at a higher risk of breakthrough hospitalisation, ICU admission, and death.…”
Section: Discussionmentioning
confidence: 99%
“…While vaccines may be sufficient to safeguard most immunocompetent individuals against severe COVID-19, the risk for the immunocompromised individuals described in this study underscores the urgent need for additional preventive measures against COVID-19 in this vulnerable population. The impact of COVID-19 on immunocompromised individuals is not surprising, as they are known to have impaired immune responses to vaccines, including lower antibodies levels, reduced neutralisation activity, 37 and shorter duration of protection, 22 often remaining insufficiently protected even after booster doses. 22 , 23 Previous retrospective cohort studies in Canada 24 and the United Kingdom, 38 , 39 which included the early phase of the Omicron period, showed that fully vaccinated immunocompromised individuals were at a higher risk of breakthrough hospitalisation, ICU admission, and death.…”
Section: Discussionmentioning
confidence: 99%